Polycystic Ovary Syndrome: A Brief Review with Recent Updates - Shermin, Shahana; Noor, Aysha; Jahan, Samsad (Delta Medical College Journal, 2020)
Polycystic ovary syndrome (PCOS) is a chronic, complex and the most common endocrine disorder observed in women of reproductive age. This syndrome is heterogeneous by nature and is characterized by a combination of signs and symptoms of androgen excess and ovarian dysfunction. It is a significant public health issue. PCOS is associated with many comorbidities and also has a number of long-term metabolic and other consequences. The prevalence is quite high and is increasing day by day. It is a syndrome to be prevented by awakening awareness both in health workers and patients. There are many areas of controversies starting from its diagnosis, pathogenesis, consequences and treatment modalities. This review is an attempt to summarize the evolution of the diagnosis and current management guidelines and also to look into the future approaches. An extensive search was made through the Cochrane database, available systematic reviews and meta-analyses and recent international guidelines for providing an updated scientific overview of PCOS. Delta Med Col J. Jul 2019 7(2): 84-99